2018
DOI: 10.1186/s13063-018-2879-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of modified transalveolar sinus floor elevation and osteotome sinus floor elevation in posterior maxillae: study protocol for a randomized controlled trial

Abstract: BackgroundImplant placement in the posterior maxilla is often complicated by the insufficient bone volume. While transalveolar sinus floor elevation (TSFE) has been proven as a predictable surgical procedure to increase the bone height in the posterior maxilla, questions in regard to the necessity of the bone grafting during the sinus lift and the question of whether TSFE could be performed when the residual bone height is below 5 mm are still debated. Furthermore, high-quality evidence comparing the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Out of the 11 studies that were shortlisted for thorough evaluation, two more were excluded[ 24 25 ] due to unmatched parameters. One study[ 26 ] was excluded due to unpublished results, while two studies[ 27 28 ] were not included because they reported the use of lateral approach procedure [ Table 3 ]. Finally, an inclusion of 6 studies[ 29 34 ] was possible for meta-analysis [ Supplementary Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 11 studies that were shortlisted for thorough evaluation, two more were excluded[ 24 25 ] due to unmatched parameters. One study[ 26 ] was excluded due to unpublished results, while two studies[ 27 28 ] were not included because they reported the use of lateral approach procedure [ Table 3 ]. Finally, an inclusion of 6 studies[ 29 34 ] was possible for meta-analysis [ Supplementary Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Cho et al [19] conclude that adjunctive bone grafting is still indicated for cases requiring more than 2-3 mm of bone augmentation. Nevertheless, the evidence about the necessity of bone graft when residual bone height is below 5 mm is still controversial [22].…”
Section: Discussionmentioning
confidence: 99%
“…Autogenous bone grafts are considered the gold standard, however, to reduce the morbidity of the donor area, tricalcium phosphate was the first bone substitute to be successfully applied for sinus floor elevation and some studies have registered the improvement in the postoperative period; limited pain and fewer complications were noted [21]. Nevertheless, the necessity of grafting material to maintain the space for new bone formation after elevating the sinus membrane by using the crestal approach remains controversial [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, older patients also exhibited a lower volume, regardless of sex and edentulism. Zhao et al (2018), studied the elevation of the floor of the transalveolar sinus. 120 patients were selected who needed implant placement in the posterior regions of atrophic jaws.…”
Section: Discussionmentioning
confidence: 99%